The methodology of the Hooded Crow’s (Corvus cornix L.) colour ringing and the previous results - Kövér, László; Juhász, Lajos (Acta Agraria Debreceniensis, 2012)
The Hooded Crow (CorvuscornixL.) have moved in several Hungarian cities in the last few decades. It is breeding in Debrecen since 1959, and nowdays it’s presence can be detected at all points of the city, it is an permanent breeding species of the bird fauna. Our knowledge about the nature of urban races, including motion patterns, area fidelity is sufficiently incomplete. The aim of our research is to answer these questions by using our colour-ring program. In this study we present in details the methodology of Hooded Crow’s colour-ring program in urban area, and we also report our previousachievements.